Hubungan antara Persepsi Penyakit dengan Manajemen Diri pada Penderita Hipertensi - Hamiidah, Shofia Nurmalita; Noviana, Uki; Haryani, Haryani (PSIK FKKMK UGM, 2024)
Background: Hypertension is suffered widely in national and global communities. Implementing hypertension self-management is one of the method to maintain blood pressure level. One of the factors in maintaining self-management compliance in people with hypertension is by examining the illness perception. However, there are differences in research results which scrutinize the correlation between illness perception and the level of self-management in patients with hypertension.Objective: To determine the correlation between illness perception and self-management in patients with hypertension in the working area of the Mlati II Public Health Center, Sleman, Yogyakarta.Methods: This research was quantitative research using cross sectional analytical design. The sample in this study amounted to 121 respondents who were selected using proportionate stratified random sampling method to determine the number of respondents from each village and purposive sampling to determine respondents. The inclusion criteria in this study were people with hypertension in the working area of the Mlati II Public Health Center, aged 18-64 years, and had a blood pressure of ≥140/90 mmHg. This study used the Brief Illness Perception-Questionnaire (BIP-Q) questionnaire to measure illness perception and the Hypertension Self-Management Behavior Questionnaire (HSMBQ) to measure self-management in people with hypertension. The Spearman rank test was used to determine the correlation between illness perception and self-management in people with hypertension. Results: Among respondents, there were people who had a positive illness perception as much as (34,7%), and had a high level of self-management as much as (50,4%). Spearman rank test result was r = 0,055 with p value = 0,551.Conclusion: There is no correlation between illness perception and self-management in patients with hypertension in the working area of the Mlati II Public Health Center, Sleman, Yogyakarta. There might be another factors that affect self-management in patients with hypertension.INTISARILatar belakang: Hipertensi banyak diderita oleh masyarakat secara nasional maupun global. Upaya dalam menjaga tekanan darah, salah satunya dengan menerapkan manajemen diri hipertensi. Salah satu faktor dalam menjaga kepatuhan manajemen diri pada penderita hipertensi adalah persepsi penyakit. Namun, terdapat perbedaan hasil penelitian sebelumnya mengenai hubungan antara persepsi penyakit dengan tingkat manajemen diri pada penderita hipertensi.Tujuan: Penelitian ini bertujuan untuk menganalisis hubungan antara persepsi penyakit dengan manajemen diri pada penderita hipertensi di wilayah kerja Puskesmas Mlati II, Sleman, Yogyakarta.Metode: Penelitian ini merupakan penelitian kuantitatif dengan desain analitik cross sectional. Sampel pada penelitian ini berjumlah 121 responden yang dipilih menggunakan metode proportionate stratified random sampling untuk menentukan jumlah responden dari setiap desa dan consecutive sampling untuk menentukan responden. Kriteria inklusi pada penelitian ini adalah penderita hipertensi di wilayah kerja Puskesmas Mlati II, berusia 18-64 tahun, dan memiliki tekanan darah ≥ 140/90 mmHg. Persepsi penyakit diukur menggunakan kuesioner Brief Illness Perception-Questionnaire (BIP-Q) dan manajemen diri pada penderita hipertensi diukur menggunakan Hypertension Self-Management Behavior Questionnaire (HSMBQ). Uji Spearman Rank digunakan untuk mengetahui hubungan antara persepsi penyakit dengan manajemen diri pada penderita hipertensi.Hasil: Sebanyak 40,5% responden penelitian memiliki persepsi positif terhadap penyakitnya dan sebanyak 50,4% responden memiliki tingkat manajemen diri dengan kategori tinggi. Hasil uji Spearman Rank didapatkan nilai r = 0,055 dan nilai p = 0,551.Simpulan: Tidak ada hubungan antara persepsi penyakit dengan manajemen diri pada penderita hipertensi di wilayah kerja Puskesmas Mlati II, Sleman, Yogyakarta. Hal ini kemungkinan karena adanya faktor lain yang memengaruhi manajemen diri pasien hipertensi.